Mycobacterium bovis epidural abscess following Bacillus Calmette-Guerin therapy for bladder cancer. Issue 4 (2nd October 2019) - Jain, Hanish; Gada, Kunal; Zaidi, Syed; Asiago-Reddy, Elizabeth; Eranki, Ambika
Abstract: Bacillus Calmette-Guerin (BCG) is derived from attenuated Mycobacterium bovis . It is the most common intravesical immunotherapy for treating early stage bladder cancer. Pott's disease is a form of mycobacterial infection that involves the vertebrae. This case highlights an unusual presentation of epidural abscess infection with M. bovis following BCG therapy for bladder cancer.